Communication between Father and Child in the Qur'an: An Examination of Surat Al-Baqarah Verse 132-133 and its Implication for Children's Akidah Education - Mhd. Fadhli Suteja; Charles Charles; Arman Husni; Iswantir Iswantir (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
News about sexual abuse experienced by children because their biological father or stepfather abused their own children. Indonesia today is ranked third in the world for the phenomenon of fatherlest or father absent in child development. This study aims to examine father-child communication in surah Al-Baqarah verses 132-133 and its implications for children's creed education. This research uses library research method with qualitative approach. This study examines the main source, namely the book of tafsir al Misbah written by M. Quraish Shihab and various other relevant reference sources. The research data was analysed using content analysis technique, to examine the meaning of the verse in depth by understanding the context of father and child communication in tafsir al-Misbah and its relation to children's creed education. The result of this research is that fathers play a very important role in the development of their children, as exemplified by Prophet Ibrahim a.s and Prophet Ya'kub a.s as a father to his children, and communication between fathers and children greatly affects the child's creed education.